Community Social Education in the Perspective of the Hadith of the Prophet Muhammad SAW - Murjazin, Murjazin; Nurhuda, Abid; Aziz, Thariq (Universitas Muhammadiyah Mataram, 2023)
Islam is the most comprehensive religion, not only teaching and educating regarding the relationship between humans and their gods, but it also teaches how humans relate to humans. So special and effective education is needed as an effort to achieve harmony among people, one of which is social education. The material for this special message can be taken from the main sources of Islamic teachings, including the Hadith of the Prophet, so the purpose of this research is to describe the Values of social education, it is hoped that the community will be able to know and understand, practice as well as make their values truly embedded in themselves so that they become one personality in the framework of fostering an Islamic social life. The method used is a literature study with a sociological approach to suit the context. After all the data is collected, then reduced and its contents are analyzed to fit the relevant theme, and finally concluded. The results of the study show that the values of Community Social Education in the Perspective of the Hadith of the Prophet Muhammad SAW include interacting with and helping fellow human beings, both Muslims and non-Muslims. Apart from that, there is also a prohibition against being individualistic to create goodness and happiness not only in this world but also in the hereafter.